SWOT Analysis of Indonesian Tax Administration Innovation in the Digitalization Era - Notika Rahmi; Damith Gangodawilage (Yayasan Ilomata, 2022)
With the innovation in tax administration services in Indonesia in the digitalization era, it is hoped that it can increase taxpayer compliance and is expected to continuously have a positive effect on state revenues. The purpose of this study is to analyze what are the strengths, weaknesses, opportunities and threats in the implementation of tax administration innovations in Indonesia in the Digitalization Era. The research method used is qualitative with a descriptive approach. The results of the study show that the strengths and opportunities that can be utilized are the reliability of human resources that have been fulfilled, as evidenced by the satisfaction index of DGT service users reaching a scale of 4.1. Technology that can still be developed is also a strength. The high participation of taxpayers in following the innovation policy of tax administration is a very big opportunity with the number of manual SPT users recorded which has decreased by 88.8% in the last five years. Weaknesses and threats encountered are the lack of maintenance on the server where server downs often occur during the deadline for reporting SPT. Taxpayers also admitted that they had not fully received directions on how to operate the new tax administration system. Taxpayers need to adapt to the digitalization that is being carried out. So it is the government's duty to pay extra attention to the understanding of taxpayers in the application of the digital tax administration system.